PENGARUH LAYANAN KONSELING INDIVIDUAL TERHADAP PENERIMAAN DIRI WARGA BINAAN ANAK (KASUS NON NARKOBA) DI LAPAS ANAK PEKANBARU - Kristin Imelda; Zulfaan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the effect of individual counseling services on self-assessment of child assisted citizens (non-drug cases) dilapas anak pekanbaru. The research method used is pre experimental method using The One Group Pretest-Posttest Design pattern. This research is done twice before the experiment (pre test) and after the experiment (post test) with one group of the subject. The data analysis used in this research Qualitative analytical descriptive. The subject of this research is selected using non-probability sampling technique with purposive sampling method of 5 non-drug users. This research is conducted by giving individual counseling service 5 times meeting. The analysis used is to find data obtained from interviews, field notes, and other materials.Keyword: Self Acceptance, Individual Counseling Services, Child Supported Citizens